The work revolution : - Clow, Julie (Wiley, 2012)
Julie Clow articulates the rules we follow today in our work force, the reasons they no longer work, and what we can do instead. The Work Revolution deconstructs the magic behind thriving, liberated organizations (such as Google) into clear principles that any individual, leader, and organization can adopt to create sustainable and engaging lives.